(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to identify (effective classroom management among members of the educational staff and its relationship to school dropout among primary school students from the point of view of primary school principals. Based on that, three objectives were formulated to identify: the level of effective classroom management among members of the educational staff, and the level of school dropout among primary school students And the relationship between them, and to achieve the objectives of the research, the researcher prepared the scale of classroom management, which consisted of (20) paragraphs, and the scale of school dropout, which consisted of (20) paragraphs. After that, the researcher applied the research scale to the sample individuals, as the research sample amounted to (100) individuals from primary school principals who were chosen from the basic research sample of (646) individuals at a rate of (15%), and after completing Applying the research scale to the sample, the data was transcribed and analyzed using the SPSS computer program. The research results revealed that primary school teachers are competent in classroom management, while primary school students do not suffer from school dropout. There is an inverse relationship between classroom management and school dropout. The researcher recommended adopting the research tool to reduce the phenomenon of school dropout..